(untitled) (Proceedings of International Educators Conference, 2022)
In the article, the scope of influence of the source of information in increasing the effectiveness of education is expanded, as well as ensuring both mastery and activity of the student-student, in a new approach, the student is able to express his opinion freely, express his opinion at this stage of the lesson process, and get answers to the questions that arise, in a new approach. if there are any mistakes, to become an active subject who personally participates in its elimination, to achieve the need to have an independent opinion and a personal position, to use practical training and seminars in the process of forming knowledge, skills and abilities in students, to organize training activities as much as possible the issues of the need to raise the status and organize the activities are interpreted.